A Comparison between the theory and the practice on the evaluation process of the foreign language department at the University of El Salvador : during semester I and II, 2003 - Benavides Espinal, Cesia Jemimma (Universidad de El Salvador, 2004)
Constantly, the language teachers devote precious time to report the progress and to get the most benefits from language learners’ performance on a subject. But 5 we do not have enough time to meditate on the deep importance of the processes, the evaluation techniques and the people involved in the educational field. For that reason the focus of this graduation project intends to expand, into some degree, the problematic that is taking place in the Foreign Language Department at the University of El Salvador semester I and II, 2003, regarding the lack of criteria in the Policy of this institution. Essentially, they have to do with the type of training for professors, the contribution of tests results, and considerations on improving the teaching-learning process throughout the Evaluation techniques. Moreover, many opinions were included to have a reliable sample to be mixed with the bibliographical information. In summary, it is expected that teachers, students as well as other people engaged in the foreign language teaching field take the most significant part of this argumentative essay.